Toward a Metamodel Quality Evaluation Framework: Requirements, Model, Measures, and Process - Kudo, Taciana Novo; Bulcão-Neto, Renato F.; Vincenzi, Auri M. R. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
The quality of metamodel considerably affects the models and transformations that conform to it. Despite that, there is still little discussion about a comprehensive form to evaluate the quality of metamodels and its consequences in model-driven development processes. This paper proposes a metamodel quality evaluation framework called MQuaRE (Metamodel Quality Requirements and Evaluation). MQuaRE comprises metamodel quality requirements and measures, a quality model, and an evaluation process, with the evident influence of international standards for software product quality, such as ISO/IEC 25000 series. We present a simple use case of MQuaRE describing how requirements, measures, and the quality model should be used during the evaluation process of a metamodel for software patterns. Among other benefits, MQuaRE can help determine final metamodel quality, decide on the acceptance of a metamodel, and also assess the positive and negative aspects of a metamodel, contributing to its quality evolution.